2014
DOI: 10.1111/adj.12166
|View full text |Cite
|
Sign up to set email alerts
|

After hours presentation of traumatic dental injuries to a major paediatric teaching hospital

Abstract: Background: Thorough record taking of traumatic dental injuries is vital. This study aimed to assess the efficacy of a structured paper history for this purpose. Furthermore, the aetiology and epidemiology of these injuries were investigated, with the aim of formulating appropriate preventive guidelines. Methods: A six-month audit of traumatic dental injuries presenting after hours was undertaken at The Children's Hospital at Westmead. A structured paper history form was subsequently created, and the data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 18 publications
9
33
0
Order By: Relevance
“…More Australians die of oral cancer than cervical cancer every year, making comprehensive screening of the oral cavity as important as cervical cancer screening . In addition, dental trauma and dental emergencies are commonly seen in hospital emergency departments around Australia, in which successful outcomes are highly dependent on the timeliness of correct diagnosis and management …”
Section: Introductionmentioning
confidence: 99%
“…More Australians die of oral cancer than cervical cancer every year, making comprehensive screening of the oral cavity as important as cervical cancer screening . In addition, dental trauma and dental emergencies are commonly seen in hospital emergency departments around Australia, in which successful outcomes are highly dependent on the timeliness of correct diagnosis and management …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Some studies regarding the incidence of dental injuries have not reported any root fractures although it is not clear whether they did not occur or they were just not considered in the study design, such as retrospective studies in which only clinical examinations were performed and radiographs were not taken. [1][2][3][4][5][6] Some studies regarding the incidence of dental injuries have not reported any root fractures although it is not clear whether they did not occur or they were just not considered in the study design, such as retrospective studies in which only clinical examinations were performed and radiographs were not taken.…”
mentioning
confidence: 99%
“…A factor lacking research on both a family and community levels was physical safety. Dental trauma has been most frequently associated with falls and can also be due to assaults, animal attacks and lack of parental supervision . The prevalence and aetiology of dental trauma in children has been explored in international literature .…”
Section: Discussionmentioning
confidence: 99%
“…This domain is described by factors such as neighbourhood stability and safety. Unsafe community environments could lead to dental trauma, and previous studies have found dental trauma is more likely to occur during social activities on the weekend and school holidays . Similar to family composition, the association between social environment and physical safety could be investigated using national datasets assessing community environment and neighbourhoods…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation